PENENTUAN LOT SIZE DENGAN MODEL DINAMIS ALGORITMA WAGNER WITHIN DI PT XYZ - Febby Chandra Adipradana; Yusraini Muharni (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2021)
Fulfillment on demand is one of the problems of uncertainty that usually afflicts a company because that the raw materials and products that are expected to be obtained at the right place and time and at a relatively low cost. PT XYZ is one of the companies located in Bogor with the process of processing mining materials in the form of gold ore as the main mineral and silver as secondary mineral in its mining operations requires some supporting materials in the form of raw materials and spare parts of hauling equipment and machinery, one of which is cone crush machine that needs more attention so that requires optimal lot sizing technique. Therefore the wagner within algorithm technique is proposed as a method that is considered to provide optimal results. The step is to analyze the cone crush machine spare part with ABC analysis to see the spare part with more attention and get two materials 1200161 and 1200172. After that, the calculation of the cost of the size of the order lot resulted in a fee of Rp. 373,915,196 for material 1200161 with a frequency of 4 times the order and Rp. 339,974,407 for material 1200172 times with a frequency of 3 times the order, making it lower than that made by the company. Therefore the implementation of Wagner within algorithm method is better because there is no cost of saving from spare parts that have been ordered with a percentage savings of 15.29% and 21.66% per year.